Radikalisme agama dalam persepektif Sosiologi Agama - Sukardiman, Sukardiman (Pusat Studi Kebudayaan Universitas Nahdlatul Ulama Nusa Tenggara Barat, 2024)
Religious radicalism is a common phenomenon found in the world community, religious and cultural differences are often used as negative energy to suppress other religious groups with the argument of the scriptures. radicalism in the name of religion seems to be justified, even though there is an error in the perspective of the holy book text, because it does not see from a historical point of view the verse came down and the social context of today's society. In this paper, the author uses the literature study method, which is an activity carried out in an effort to explore, examine, and identify and identify knowledge based on the results of previous research or studies related to radicalism in the name of religion. In the context of the sociology of religion, the essence of religion is the glue of social cohesion between humans, we can see this in the perspective given by sociological figures, such as ibn Khaldun, Max Weber, and Emile Dhurkeim. In the context of Islam itself, it also teaches about religious inclusiveness, one of which is very visible in the vision of Islamic plurality, where the prophet made a constitution called the Medina Pilgrimage which regulates the lives of three major religions, namely Christianity, Judaism and Islam. However, in the current era Islam is experiencing a global stigma, thus creating what is called Islamophobia, even though Islam is not what western people think. So the conclusion is Islam never teaches about violence, but Islam teaches about peace. Key word: religious Radicalism, Islam, Sociology of Religion.